KAJIAN VIKTIMOLOGI TERHADAP PERKARA KEKERASAN FISIK DALAM RUMAH TANGGA (STUDI PUTUSAN PN YOGYAKARTA DAN PN SLEMAN) - Zhafarina, Adlia Nur (Universitas Muhammadiyah Ponorogo, 2024)
Unequal power relations between husband and wife can lead to domestic violence, such as physical abuse, which is a form of gender-based violence, that 95% of the victims are women. Based on the annual records of the National Commission on Violence Against Women which collect data from service institutions, physical abuse is the type of violence that occurs most frequently in 2019-2022. In this research, cases of physical abuse in domestic sphere that have been decided by the Yogyakarta District Court in 2019 and the Sleman District Court in 2019 and 2020 will be studied, so that the trend pattern of domestic violence cases in the Yogyakarta District Court and the Sleman District Court can be described and presented, as well as victimology study of these cases so that it can illustrate how the process of victimization of victims can occur. Furthermore, this type of research is normative legal research which is carried out by examining secondary data with a case approach. This research find that the trend pattern of domestic violence cases in the Yogyakarta District Court and the Sleman District Court in 2019-2020 based on court decisions examined in this research shows that the majority of perpetrators of physical abuse are husbands and the victims are wives. The presence of another woman or man in a household is what dominates the cause of jealousy and suspicion in the husband or wife which results in arguments and leads to violence. The process of victimization of victims can occur due to unequal power relations between husband and wife which ends in violence. In this case, unequal power relations are the main causal factor in the occurrence of domestic violence, while the presence of another woman or man in a household is the triggering factor for arguments that lead to domestic violence in the majority of cases in the decisions of the Yogyakarta District Court and the Sleman District Court.